2007
DOI: 10.1021/jf070569k
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Procyanidins in Apple Polyphenol Are Main Active Components for Inhibition of Pancreatic Lipase and Triglyceride Absorption

Abstract: Inhibitory effects of apple polyphenol extract (AP) and procyanidin contained in AP on in vitro pancreatic lipase activity and in vivo triglyceride absorption in mice and humans were examined. AP and procyanidin considerably inhibited in vitro pancreatic lipase activity. However, polyphenols, except for procyanidin, in AP (i.e., catechins, chalcones, and phenol carboxylic acids) showed weak inhibitory activities on pancreatic lipase. Procyanidins separated by normal-phase chromatography according to the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
225
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 32 publications
15
225
0
2
Order By: Relevance
“…The present results show that the oral intake of GSPE significantly blocked the increase in plasma TAG levels induced by lard oil ingestion in control animals. This blockade of plasma TAG has also been described with PA from apples (8) in mice loaded with maize oil, in which the blockade was as rapid as that observed in the present experiment (1 h). In the present study, the reduction in plasma TAG levels was similar to the reductions observed in male normolipidaemic rats (6) and mice (10,11) after performing acute GSPE treatment and in dyslipidaemic rats (7) after performing chronic GSPE treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present results show that the oral intake of GSPE significantly blocked the increase in plasma TAG levels induced by lard oil ingestion in control animals. This blockade of plasma TAG has also been described with PA from apples (8) in mice loaded with maize oil, in which the blockade was as rapid as that observed in the present experiment (1 h). In the present study, the reduction in plasma TAG levels was similar to the reductions observed in male normolipidaemic rats (6) and mice (10,11) after performing acute GSPE treatment and in dyslipidaemic rats (7) after performing chronic GSPE treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, PA repress the secretion of both synthesised, endogenous TAG and TAG absorbed from the diet. Several authors have reported that CM and lipid absorption cause the hypolipidaemic actions of PA, but only on the basis of indirect evidence or in vitro experiments (8,9) . The expression of the selected genes related to FA and TAG metabolism as well as those of the CM assembly was not modified in the intestinal mucosa at 1 or 5 h after GSPE administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced absorption of dietary fat from the intestine by the inhibition of digestive lipases, especially pancreatic lipase, is an approach to decreasing the risk of obesity [15]. The presence of pancreatic lipase inhibitors has recently been reported in some edible fruits, including black chokeberry [12,13,21,[25][26][27][28][29]. Inhibition of this enzyme by fruits is attributed to the phenolic compounds, such as proanthocyanidins [12,21,27], ellagitannins [25,26], anthocyanins [13,28], and flavones [29].…”
Section: Discussionmentioning
confidence: 99%
“…The mDP of proanthocyanidins occurring in chokeberry fruit was determined as 59 [36] or in the acetone fruit extract as 19 [34]. The published studies have shown that anti-lipase activity of proanthocyanidins depends upon the degree of polymerization and more potent effect was observed for higher DP [27,37]. For example, the IC 50 values determined with the use of 4-MUO as the substrate were as follows: for dimer >125 μg/ml, but 32.9 and only 0.9 μg/ml for trimer and procyanidins over nonamer, respectively [27].…”
Section: Discussionmentioning
confidence: 99%